Do "lie scales" measure lying? Evaluating applicant honesty on social desirability scales - Hughes, Angus; Holtrop, Djurre; Dunlop, Patrick; Steedman, Grace; Chan, Joan (2019)
Aim: Between 30-50% of job applicants are thought to ‘fake’ on personality measures, representing a challenge to the validity of these assessments by practitioners in the selection process (Griffith, Chmielowski, & Yoshita, 2007). Social desirability (SD) scales, sometimes known as ‘lie scales’, are frequently embedded in self-reported personality measures to identify job applicants responding dishonestly (Goffin & Christiansen, 2003). These scales are scored by tallying the number of positive responses to excessively virtuous and unlikely items (e.g. “There has never been an occasion when I took advantage of someone else”). However, there remains debate in the literature as to how effective SD scales really are in identifying dishonest responding. For example, De Vries et al. (2018) have argued that items in SD scales may not be read literally, but are instead endorsed in good faith to signal authentic virtuosity. We therefore tested three central hypotheses using a novel speak-aloud protocol methodology: A) Are item responses keyed as “dishonest” by SD scales evaluated as less honest?; B) Are overall SD scale scores associated with lower honesty on responses to personality scale items?; C) Are these effects increased in high-stakes job application settings?